2017
DOI: 10.1016/j.virol.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Ebola virus VP35 blocks stress granule assembly

Abstract: Stress granules (SGs) are dynamic cytoplasmic aggregates of translationally silenced mRNAs that assemble in response to environmental stress. SGs appear to play an important role in antiviral innate immunity and many viruses have evolved to block or subvert SGs components for their own benefit. Here, we demonstrate that intracellular Ebola virus (EBOV) replication and transcription-competent virus like particles (trVLP) infection does not lead to SG assembly but leads to a blockade to Arsenite-induced SG assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 60 publications
0
47
1
Order By: Relevance
“…Overexpression of G3BP1 induces SG formation (Tourriere et al, 2003). Cleavage of G3BP1 by viral protease or sequestering of G3BP1 by viral proteins inhibits formation of SGs (Le Sage et al, 2017;Nelson et al, 2016;White et al, 2007). Here we observed that while knockdown of G3BP1 enhanced PEDV replication, overexpression of G3BP1 reduced PEDV replication in Vero cells.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Overexpression of G3BP1 induces SG formation (Tourriere et al, 2003). Cleavage of G3BP1 by viral protease or sequestering of G3BP1 by viral proteins inhibits formation of SGs (Le Sage et al, 2017;Nelson et al, 2016;White et al, 2007). Here we observed that while knockdown of G3BP1 enhanced PEDV replication, overexpression of G3BP1 reduced PEDV replication in Vero cells.…”
Section: Discussionmentioning
confidence: 59%
“…Some virus infections cause SGs and the formation of SGs is considered as an indication of an antiviral innate response that limits translation of the viral genes (Onomoto et al, 2014). Many viruses have evolved strategies to overcome the antiviral effect of SGs by degrading or sequestering its key components such as G3BP1 or TIA-1/TIAR to prevent the formation of SGs (Emara and Brinton, 2007;Humoud et al, 2016;Le Sage et al, 2017;Nelson et al, 2016;White et al, 2007;White and Lloyd, 2011). The nonstructural protein 1 (NS1) of influenza A virus (IAV) inhibits eIF-2α phosphorylation mediated SGs by blocking PKR activation (Khaperskyy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…mRNAs from filoviruses (those encoding VP35, VP30, VP24 and L) contain initiation sequences similar to those found in the host proteins that remain present after cellular stress, thus shifting host translation towards the production of viral mRNAs, a phenomenon that is supported by the lack of stress granule formation in EBOV-infected cells [115][116][117] .…”
Section: Convalescent Serummentioning
confidence: 99%
“…These organelles also regulate mRNA stability and have antiviral functions (reviewed in reference 138). Viruses use various strategies to disrupt or block stress granules; for example, Ebola virus inhibits SG formation (139), influenza virus sequesters double-stranded RNA (dsRNA) to prevent SG initiation (140), and poliovirus 3 C protease cleaves a major SG protein, Ras GTPase-activating protein-binding protein 1 (G3BP1) (141). The RNA-binding PARP12 and -13 are found in stress granules, where PARP12 is responsible for MARylation of various proteins such as the argonaute proteins, G3BP1, and TIA-1 (36).…”
Section: Parps As Transcription Factor Coactivators/corepressorsmentioning
confidence: 99%